التنظيمات التجارية بين حرية التجارة المكفول والضوابط الشرعية. دراسة في الآليات والضوابط - سعيدي, زيان (جامعة الوادي university of eloued, 2022)
البحث محاولة للكشف عن المقاربة التي وضعها الإسلام بين ضمان حق ممارسة النشاط التجاري وكفالة الحرية في هذا المجال نوعا وكما، ومقدارا في الأرباح والأسعار، ومحلا وتنقلا للاتجار، وبين القيود التي وضعها الإسلام ترشيدا للسلوك التجاري وضبطا للنشاط التجاري الذي تنتظم عنده جميع مصالح الأطراف المتعاقدة. فلا الحرية المكفولة تتخذ مطية للفساد والإفساد التجاري ولا القيود الضابطة تتخذ مطية للتضييق والحرج. وقد وزع الإسلام هذه الضوابط التي احتكم إليها في تنظيم النشاط التجاري وفق المقاربة المشار إليها بين توجيهات وإرشادات حاثة وبين قواعد تنظيمية ووسائل عملية واقعية وهي جملة الآليات مستهدفا بذلك الوصول بالتجارة إلى جعلها وسيلة مؤثرة في التنمية الاقتصادية والاجتماعية المنشودة. The research tries to reveal the approach that Islam established between, firstly guaranteeing the right to exercise the commercial activity, ensuring freedom in this area based on quality and quantity, the amount in profits, prices, residence, and the transportation to do the commerce; and secondly restrictions established by Islam rationalizing the commercial conduct and controlling the business activity which holds the interests of the contracting parties... so that this guaranteed freedom is not a cause for corruption and the seizing restrictions are not a cause for constriction and awkwardness. Islam invokes these restrictions that it has distributed to organize the commercial activity following the indicated approach between persuasive direction and guidance, regulations, practical and realistic means and that is the combination of mechanisms targetting the goal of making commerce an effective mean for the desired economic and social development
مقال
Keywords: التجارة، الحرية، الأسواق، القواعد التنظيمية، الضوابط الشرعية.; trade, freedom, markets, regulatory rules, Legal controls.